Genetic improvement and related activities. Improvement of individual characters. Tolerance to acid soils - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
During 1986 screening of advanced bean lines for efficiency at low levels of P and for tolerance to high levels of Al saturation continued. A review of data from 8 yr. of screening indicated that the genetic variability of beans for these 2 characteristics is low. Furthermore, the data suggest that efficiency and tolerance are determined by separate mechanisms. The principal group screened was comprised of small black- and red-seeded materials of growth habit types II and III, adapted to Central America and the Caribbean. Mean yields of lines of growth habits II and III showing outstanding performance at low P levels and high Al saturation are included. (CIAT)